Propagation of Prosopis Species: Problem Perseverance and Perspectives - Ramawat, K G; Nandwani, Dilip (Annals of Arid Zone, 2016)
Prosopis species are predominant components of arid-land vegetationbut they are degenerated as biotic pressure has caused large scaledeforesta tion. Plant tissue culture has been proved successful inregeneration of a large number of tree species. However, Prosopisspecies are recalcitrant to regenerate and efforts made by variousworkers to regenerate and propagate Prosopis are discussed in thelight of achievements made in the laboratory.